Opinion on the follow‐up of the re‐evaluation of sorbic acid (E200) and potassium sorbate (E202) as food additives. (1st March 2019) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Fürst, Peter; Gürtler, Rainer; Gundert‐Remy, Ursula; Husøy, Trine; Mennes, Wim; et al.
Abstract: In this opinion, the EFSA Panel on Food Additives and Flavourings (FAF Panel) was requested by the European Commission to carry out a scientific evaluation of an extended one‐generation reproductive toxicity study (EOGRTS) to determine whether it would allow reconsideration of the temporary group acceptable daily intake (ADI) for sorbic acid (E 200) and potassium sorbate (E 202), established by the Panel on Food Additives and Nutrient Sources added to Food (ANS Panel) in 2015. From the EOGTRS, the FAF Panel identified a lower confidence limit of the benchmark dose (BMDL) of 1, 110 mg sorbic acid/kg body weight (bw) per day. By applying a default uncertainty factor of 100, the Panel established a group ADI expressed as 11 mg sorbic acid/kg bw per day for sorbic acid (E 200) and its potassium salt (E 202). In addition, European Commission asked EFSA to review a report on the 'Stability of sorbic acid (E 200) and its potassium salt (E 202) during food processing and storage' provided by industry. No new information was provided in this report, and therefore, in this opinion, there was no re‐assessment of the EFSA ANS opinion conclusions from 2015 regarding the stability of sorbates in food.